Overview of developed core and mini core collections and their effective utilization in cultivated rice and its related species (Oryza sp.)—A review. (18th May 2022) - Raturi, Dhananjay; Chaudhary, Manju; Bhat, Vishnu; Goel, Shailendra; Raina, Soom Nath; Rajpal, Vijay Rani; Singh, Apekshita
Abstract: Genus Oryza consists of two cultivated and 21 related wild species. Cultivated rice is not only the staple food of the majority of the countries in the world, but it also serves as a model crop for genomic studies. The rice germplasm is conserved in different gene banks around the world, which can be accessed for plant breeding programmes aiming to improve rice varieties. However, the ever‐increasing number of accessions poses problem of the phenotypic and genotypic characterization of the germplasm. Therefore, to speed up characterization and utilization of germplasm, the concept of core collection ( 10–20% of total base collection) was developed which provides maximum diversity in limited number of accessions. Similarly, a mini core collection ( 1–2% of the entire collection) is constructed retaining maximum diversity to provide wider genetic coverage in manageable numbers. The present review summarizes the current information on different core and mini core sets developed for varied purposes from world rice collections using different strategies.